A novel fate and transport model for evaluating the presence and environmental risk of per-/poly-fluoroalkyl substances (PFASs) among multi-media in Lingang hybrid constructed wetland, Tianjin, China. (March 2022) - Xu, Zhuoqi; Ma, Xiaodong; Wei, Zizhang; Ren, Gengbo; Wu, Zhineng; Man, Quanli; Zhou, Bin; Liu, Honglei; Yuan, Dekui
Abstract: Accurately revealing and predicting the presence and risks of per-/poly-fluoroalkyl substances (PFASs) in constructed wetlands (CWs) is great significant for the construction and management of CWs, but very challenging. In this work, a novel fate and transport model was for the first time established to evaluate the spatially continuous distribution and environmental risks of PFASs among multi-media in Lingang hybrid CW fed by industry tailwater. 20 PFASs were detected from the Lingang CW, and the total concentration of the detected PFASs in water and sediments were in the range of 38.94–81.65 ng/L and 1.23–4.31 ng/g, respectively. PFOA, PFOS and PFBS were the main pollutants in water and sediments. A fate and transport model describing the distribution characteristics and fate of PFASs in Lingang hybrid CW was constructed, and its reliability was veriﬁed. The simulated results suggested that PFASs were mainly accumulated in sediments and long-chain PFASs were more easily adsorbed by sediments compared with short-chain PFASs. According to the principal component analysis-multiple linear regression (PCA-MLR), PFASs mainly came from the tailwater from the surrounding sewage treatment plants. Besides, the environmental risks were predicted by this novel model, suggesting that the risks still cannot be neglected due to the accumulation and continuous input of PFASs although the environmental risks of Lingang CW were low. This work provides a novel model for the understanding of presence and risks of PFASs among multi-media in CWs. Graphical abstract: Image 1 Highlights: A novel model was constructed to present the occurrence and risks of PFASs in CW. PFOA, PFOS and PFBS were the main pollutants in water and sediments. Long-chain PFASs were more prone to transfer from water to sediments. Environmental risk of PFASs of this CW cannot be neglected.